Sexual Dimorphism in Glucose and Lipid Metabolism during Fasting, Hypoglycemia, and Exercise - Hedrington, Maka S.; Davis, Stephen N. (Frontiers in Endocrinology, 2015)
Sexually dimorphic physiologic responses occur during fasting, hypoglycemia and exercise. The areas covered in this mini review include studies that have used isotopic tracer methods and/or euglycemic clamp studies to investigate substrate metabolism during the above common physiologic stress. Women have greater reliance on lipid metabolism during fasting, hypoglycemia and exercise while men exhibit preference of carbohydrate utilization. Plasma glucose concentrations were shown to be lower, while free fatty acids (FFA) and lipolysis higher in women compared to men after fasting. Hypoglycemia resulted in significantly reduced epinephrine, norepinephrine, glucagon, growth hormone, pancreatic polypeptide and hepatic glucose production responses in females as compared to males. Sexual dimorphism during exercise was demonstrated by higher glycerol and FFA responses in women compared to men and higher carbohydrate oxidation rate in men. Mechanisms that can increase lipolytic rates in women include higher total fat mass, enhanced lipolytic sensitivity to epinephrine and increased activation of β adrenergic receptors.